1999
DOI: 10.1093/tropej/45.2.115
|View full text |Cite
|
Sign up to set email alerts
|

The impact of breastfeeding practices on respiratory and diarrhoeal disease in infancy: a study from Sri Lanka

Abstract: A hospital-based descriptive recall study was conducted to assess the relationship, if any, between breastfeeding practices and morbidity from respiratory and diarrhoeal diseases in infants. A total of 343 infants (285 admitted patients and 58 controls) were recruited. Clinical and sociodemographic data and details regarding breastfeeding practices, timing of the first respiratory or diarrhoeal illness, and the timing of the first admission for a respiratory or diarrhoeal illness, were carefully documented. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 0 publications
3
26
2
Order By: Relevance
“…This supports findings of previous studies in the country, which revealed that the knowledge and management practice of many aspects of diarrhoea was grossly deficient, particularly among the younger and less educated mothers 3,15 . The lack of breast-feeding was not significantly associated with diarrhoeal episodes in our study, in contradiction to the findings of most studies reporting that diarrhoea is much more common in non-breast-fed children than in breast-fed children 12,13 . This may be real or may be due to sampling errors or variations.…”
Section: Discussioncontrasting
confidence: 99%
“…This supports findings of previous studies in the country, which revealed that the knowledge and management practice of many aspects of diarrhoea was grossly deficient, particularly among the younger and less educated mothers 3,15 . The lack of breast-feeding was not significantly associated with diarrhoeal episodes in our study, in contradiction to the findings of most studies reporting that diarrhoea is much more common in non-breast-fed children than in breast-fed children 12,13 . This may be real or may be due to sampling errors or variations.…”
Section: Discussioncontrasting
confidence: 99%
“…The second mechanism is to have less disease burden due to infections, which reduces food intake and increases energy expenditure through fever and loss of nutrients through stools. Some of these effects have been confirmed in earlier studies in other settings (Lopez-Alarcon et al, 1997;Zaman and Baqui, 1997;Perera et al, 1999;Baker et al, 2006;Gunnarsdottir et al, 2009;Singh et al, 2009).…”
Section: Discussionsupporting
confidence: 58%
“…The outcome of exclusive breastfeeding is to reduce the rates of morbidity, and mortality in early infancy has been extensively reviewed (Lopez-Alarcon et al, 1997;Zaman and Baqui, 1997;Perera et al, 1999;Baker et al, 2006;Black, 2008). Appropriate breastfeeding of newborns under 2 years of age has the greatest potential impact on child survival of all preventive interventions, with the potential to prevent 1.4 million deaths in the developing countries (Lauer et al, 2007;UNICEF, 2008;LancetSeries, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…72 Moreover, replacement of colostrum with pre-lacteal feeds increased the risk of neonatal mortality in The Gambia, 73 and mixed supplemental feeding was associated with increased rates of diarrhea, 74,75 respiratory illness, 76,77 and mother-to-child transmission of HIV. 78 Although breastfeeding is common, immediate and exclusive breastfeeding, despite its benefits, is not normal practice in many developing countries, particularly for LBW newborns.…”
Section: Moss Et Almentioning
confidence: 99%